PEMBERDAYAAN WAKAF MENURUT QANUN NO . 10 TAHUN 2007 (ANALISIS PERAN BAITUL MAL KABUPATEN ACEH TENGAH) - Hafsah, Arsyadi Ulya, Ansari Yamamah, (AT-TAFAHUM: Journal of Islamic Law, 2017)
Abstrak: This thesis aims to find out the extent of Qanun No. 10 of 2007 regulates the management of waqf, And in its application carried out by Baitul Mal Central Aceh district and see the extent of the role of waqf in improving the welfare of the Ummah in Central Aceh district. The research method used in this study is the empirical research method or known as non-doctrinal research, namely research that uses case studies. The research referred to here is research that combines primary materials in the form of direct information from Baitul Mal, Central Aceh District, while the primary sources in this study are sourced from documentation, reports, reports and books relating to the research subject including: Jurisprudence, , Researchers used Law No. 41 of 2004 concerning waqf, compilation of Islamic Law, concerning the Baitul Mal secretariat in Central Aceh district. Qanun No. 10 of 2007 concerning Baitul Mal. From the results of research conducted by researchers, it can be concluded that the empowerment of waqf based on Qanun No. 10 of 2007 (Analysis of the role of Baitul Mal Regency of Central Aceh) still less than the maximum Baitul Mal carry out the mandate to make more productive representation, while the role of waqf in advancing welfare seems to be still at the level of spiritual well-being, and have not been able to answer welfare in the social economy.Keywords : wakaf, pemberdayaan, Qanun, Baitul Mal, Aceh Tengah